Constructing Gaia: Using journals to foster reflective learning - Haigh, Martin J. (Journal of geography in higher education, 2001)
Learning journals are used to help advanced-level undergraduate students construct a personal understanding of Gaia Theory. In this context, students like the journal technique and consider it appropriate to the course. They also agree that writing journals contributes to promoting subject learning, introspection and self-awareness of their own learning processes. For the instructor, the journals provide detailed insight into the development of student learning and students' interactions with the other components of the curriculum. The journals highlight which instructional devices work, which have problems, who is affected and what learning strategies they adopt. They provide a better perspective on the extent of students' reading and reflection than is obtainable from more formal scripts. The chief problem in the use of learning journals is their bulk and the time required for assessment and analysis. The journal technique has also helped demonstrate how the Gaia Theory may provide an appropriate curriculum for the practice of constructive learning. The unorthodox ideas and contradictions of Gaia Theory successfully challenge students to think deeply, critically and self-consciously about their prior understanding of the world.